Medium-Term Visual Outcomes of Apodized Diffractive Multifocal Intraocular Lens with +3.00 D Addition Power. (3rd March 2014) - Guo, Xiaohong; Sun, Yi; Zhang, Bowen; Zheng, Danying
Abstract : Purpose . To evaluate 2-year visual acuities and questionnaire after bilateral implantation of SN6AD1 multifocal intraocular lens (MIOL) or SN60WF IOL. Methods . Patients randomly scheduled for bilateral implantation of SN6AD1 MIOL and SN60WF IOL with 2-year follow-up were enrolled. Uncorrected/corrected distance and near visual acuity, uncorrected intermediate visual acuity at 63 cm under high and low contrast, reading activity, the defocus curve, and a quality-of-life questionnaire were evaluated. Results . Each group comprised 20 patients. Uncorrected intermediate visual acuities and uncorrected near visual acuity were better in SN6AD1 group than in SN60WF group (P = 0.005, P = 0.011, and P < 0.001 ). In SN6AD1 group, the uncorrected intermediate and near visual acuities 1 year and 2 years postoperatively were reduced than postoperative 3-month outcomes, respectively. SN6AD1 group reported superior overall spectacle independence and inferior satisfaction. SN6AD1 group had a longer reading newspaper duration than SN60WF group (P = 0.036 ). When using mobile phone, SN6AD1 group had a more comfortable distance than SN60WF group (P < 0.001 ) and higher speed of reading fixed text message (P < 0.001 ). Conclusion . SN6AD1 MIOL provided a satisfactory full range of visual acuities and questionnaire performance 2 years postoperatively. One-year and 2-year uncorrected near and intermediate visual acuities of SN6AD1 MIOL were lower than those 3 months postoperatively.